Experiences of medical device innovators as they navigate the regulatory system in Uganda - Nakandi, Brenda T.; Muhimbise, Owen; Djuhadi, Ashley; Mulerwa, Martha; McGrath, Janet; Makobore, Philippa Ngaju; Rollins, Andrew M.; Ssekitoleko, Robert T. (Frontiers in Medical Technology, 2023)
Objective: A medical device must undergo rigorous regulatory processes to verify its safety and effectiveness while in use. In low-and middle-income countries like Uganda however, medical device innovators and designers face challenges around bringing a device from ideation to being market-ready. This is mainly attributed to a lack of clear regulatory procedures among other factors. In this paper, we illustrate the current landscape of investigational medical devices regulation in Uganda. Methods: Information about the different bodies involved in regulation of medical devices in Uganda was obtained online. Nine medical device teams whose devices have gone through the Ugandan regulatory system were interviewed to gain insights into their experiences with the regulatory system. Interviews focused on the challenges they faced, how they navigated them, and factors that supported their progress towards putting their devices on the market. Results: We identified different bodies that are part of the stepwise regulatory pathway of investigational medical devices in Uganda and roles played by each in the regulatory process. Experiences of the medical device teams collected showed that navigation through the regulatory system was different for each team and progress towards market readiness was fuelled by funding, simplicity of device, and mentorship. Conclusion: Medical devices regulation exists in Uganda but is characterised by a landscape that is still in development which thereby affects the progress of investigational medical devices.